Motivation during Online Classes: Analyzing Socio-Demographic Profile of Engineering Students - Prof. Dr. Mohsin Kazmi; Dr. Samar Fahd; Prof.® Dr. Muhmmad Saeed; Dr. Abdul Rauf; Syeda Sajida Firdos (Journal of Management Practices, Humanities and Social Sciences, 2022)
The study aimed to analyze the socio-demographical profile of engineering students in the context of their motivation during online classes. Engineering students (N=1616) of both genders (males N=1352 & females N=264) enrolled in 9 public sector universities of Pakistan were included in this study. The age range of the students was between 17 to 26 years. The Academic Motivation Scale (Vallerand et al., 1992) and an extensive self-structured demographical profile were used as a tool for data collection. The Academic motivation scale measured seven sub-categories of intrinsic, extrinsic, and amotivation, while the demographical sheet collected different dimensions of the personal, educational, social, and residential information. The study gathered an enormous collection of information about significant demographics of engineering students studying through online classes. According to the perspective of gender, there was no significant difference found in the motivation level of students during online classes. Access to the internet was the most significant demographic variable, positively correlated with the sub-categories of intrinsic and extrinsic motivation during an online class. This study added a unique finding in the literature that students' motivation during online classes could be increased when they have better access to internet facilities.